Promoting Language Learning Through “Transdicto”: An Alternative Design for ER+ Program - Endang Setyaningsih; Kristiandi Kristiandi; Hasan Zainnuri; Teguh Sarosa (English Department - University of Sultan Ageng Tirtayasa, 2021)
This paper aims to answer two research questions: (1) What design of an Extensive Reading program can be developed in the EFL setting with time constraints and (2) How do students respond to the design implementation. To achieve these goals, the study used Design-Based Research and, in the practice, it was carried out in 3 major phases. The initial phase was the analysis of practical problems. The second phase was literature research to inform the planning and development of the prototype design and the last phase was the implementation and reflection of the implementation of the design. The study was carried out in one semester in an English Education Department of a university in Indonesia. The study results in an alternative design to an ER+ program that is called Transdicto. Transdicto is conducted in five major steps: (1) extensive reading/ listening, (2) note-taking, (3) exploring, (4) contextualizing, and (5) transforming. Observation and interview revealed that the students responded well to Transdicto; they found the steps of the activity were relatively easy to follow, useful, and engaging